2020
DOI: 10.1017/s2045381720000167
|View full text |Cite
|
Sign up to set email alerts
|

Authority conflicts in internet governance: Liberals vs. sovereigntists?

Abstract: We analyse conflicts over norms and institutions in internet governance. In this emerging field, dispute settlement is less institutionalised and conflicts take place at a foundational level. Internet governance features two competing spheres of authority characterised by fundamentally diverging social purposes: A more consolidated liberal sphere emphasises a limited role of the state, private and multistakeholder governance and freedom of speech. A sovereigntist challenger sphere emphasises state control, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Where differences arise out of contending spheres of authority, with different views of the governance goal or common good, conflict will be especially intense (Kreuder-Sonnen & Zürn, 2020). In the cyberspace HIC, for example, some institutions (led by the US and other Western states) favor an open internet governed by multi-stakeholder institutions, while others (led by China and Russia) view an open internet as dangerous and promote strict regulation by states (Flonk et al, 2020).…”
Section: The Hic Concept As Analytical Lensmentioning
confidence: 99%
“…Where differences arise out of contending spheres of authority, with different views of the governance goal or common good, conflict will be especially intense (Kreuder-Sonnen & Zürn, 2020). In the cyberspace HIC, for example, some institutions (led by the US and other Western states) favor an open internet governed by multi-stakeholder institutions, while others (led by China and Russia) view an open internet as dangerous and promote strict regulation by states (Flonk et al, 2020).…”
Section: The Hic Concept As Analytical Lensmentioning
confidence: 99%
“…Whatever the outcome will be, it is clear that the EU is taking a more active and sovereign stance in regulating VRWE content (Flonk et al, 2023). In simultaneously loosening and broadening approaches when responding to VRWE content, the EU's current approach represents a watering down of policy ideals to assuage reactionary-right European governments.…”
Section: Discussionmentioning
confidence: 99%
“…These developments also suggest a slow but steady shift from an EU that protects individuals to do something, to an EU that protects individuals from something. These are indicative of wider securitised shifts, due to the expansion and normalisation of a counter‐extremism paradigm and the adoption of a more sovereigntist stand (Flonk et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to minimize this by targeting respondents working in specific policy areas and asking them to evaluate different international bureaucracies separately. Indeed, past research has shown that international bureaucracies may play different roles depending on the policy area (Flonk et al., 2020; Zelli and van Asselt, 2013) (see Figure 1). Specifically, we use survey data on 15 international bureaucracies active in up to four financial policy areas (monetary policy, tax policy, debt management and banking regulation).…”
Section: Methodsmentioning
confidence: 99%